Treatment of adult facial asymmetry with orthodontic therapy or orthognathic surgery: Receiver operating characteristic analysis - Yu-Chuan Tseng; Yi-Hsin Yang; Chin-Yun Pan; Szu-Ting Chou; Kai-Chieh Ou; Hong-Po Chang (Elsevier, 2014)
Background/purpose: Not all adult facial asymmetry patients are candidates for surgical correction, therefore patient assessment and selection remain major issues in diagnosis and treatment planning. This study investigated cephalometric variables for distinguishing between adult patients requiring orthognathic surgical versus nonsurgical orthodontic treatment of facial asymmetry. Materials and methods: Receiver operating characteristic (ROC) analysis was used to assess posteroanterior cephalometric measurements. The posteroanterior cephalograms of 60 patients (30 nonsurgical and 30 surgical patients) with facial asymmetry were analyzed, and 51 cephalometric measurements were obtained using computerized cephalometry. Results: Of the 51 measurements, 16 showed statistically significant differences between the two groups. Further ROC analysis was used to determine the ability of the 16 cephalometric parameters to distinguish between the two groups of patients. Optimum discriminant effectiveness was obtained from six statistically validated measurements. For a facial asymmetry patient meeting any four of the six measurement criteria, the sensitivity was 60% and the specificity was 90% in determining the need for surgical treatment. The six criteria were mandibular shift angle ≥4.1°, ∠Ra-Me-ANS ≥3.40°, ∠Zy-Me-ANS ≥5.30°, ∠GWSO-Me-ANS ≥4.90°, ∠J-Me-ANS ≥2.10°, and Go(ver)-M-ANS ratio ≥1.11. Conclusion: These six cephalometric measurements constituted the minimum number of discriminators needed to obtain optimal discriminant effectiveness of diagnosis between orthognathic surgical and nonsurgical orthodontic treatment of facial asymmetry.